Using Canadian data linkage to investigate the socioeconomic patterning of hospital burden for childbirth. (2017) - Mah, Sarah M.; Sanmartin, Claudia; Rotermann, Michelle; Khan, Saeeda; Harper, Sam; Ross, Nancy A.
No abstract available